Optimisation of mass ranging for atom probe microanalysis and application to the corrosion processes in Zr alloys. - Hudson, D; Smith, G; Gault, B (2011)
Atom probe tomography uses time-of-flight mass spectrometry to identify the chemical nature of atoms from their mass-to-charge-state ratios. Within a mass spectrum, ranges are defined so as to attribute a chemical identity to each peak. The accuracy of atom probe microanalysis relies on the definition of these ranges. Here we propose and compare several automated ranging techniques, tested against simulated mass spectra. The performance of these metrics compare favourably with a trial of users asked to manually range a simplified simulated dataset. The optimised automated ranging procedure was then used to precisely evaluate the very low iron concentration (0.003-0.018 at%) in a zirconium alloy to reveal its behaviour in the matrix during corrosion; oxygen is injected into solution and has the effect of increasing the local iron concentration near the oxide-metal interface, which in turn affects the corrosion properties of the metal substrate.